PENGGUNAAN MEDIA RODA PUTAR DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA PADA SISWA - Nur Haliza Irham; Firdaus, Andi Mulawakkan; Wahyuddin (Almeera Education, 2024)
Mathematics learning activities in class V UPT SPF SD Inpres Jongaya students are still running monton, and lack of variety in delivering material. this results in student interest in learning, student learning activities and student learning outcomes are not optimal. Actions taken to solve these problems by applying rotary wheel learning media. This research was conducted on February 23-April 4, 2024 at UPT SPF SD Inpres Jongaya. The subject of the study was class V which amounted to 28 students. This type of research is classroom action research (PTK). Data collection techniques are student interest data, student learning outcomes data, student learning activity data and teacher activity data. The types of data used are qualitative data and quantitative data. The results showed that the class average value during the pre-test reached 27.14. The average value in cycle 1 test results reached 62.14, increasing in cycle II by 81.42. Pre-action student learning interest reached 73.15 after the action increased to 82.91. It can be concluded that the use of rotary wheel media can increase interest and learning outcomes in mathematics in class V UPT SPF SD Inpres Jongaya. It is recommended that teachers can use the rotary wheel media in learning activities at school to increase student interest and learning outcomes in mathematics subjects.